Penentu Model Keputusan Investor Individu Terhadap Pengambilan Keputusan Investasi - Ardiyan, Peter; Lili Vedasiwi, Ignatia; Lestari, Henny Setyo; Leon, Farah Margaretha (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
Abstract: The purpose of this research is to examine the impact of individual investor choice models on investment decisions and to assess the validity of behavioral theory. The Structural Equation Model (SEM) analysis approach was used with the SPSS AMOS program in thisâ€quantitative research with a sample of 275 respondents. Theâ€findings suggest that prior behavior has little bearing on future investment intentions. The intention to invest is influenced by attitudes, subjective norms, and perceived behavioral control. Attitude and perceived behavioral control are influenced by financial literacy. and attitude is unaffected by previous behavior The findings of this study can assist investors in better understanding the risk of stock market losses from the shares they have purchased. Furthermore, investors must gain a better understanding of finance, investment dangers, and how to manage investment risks on the stock exchange. Â  Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh model keputusan investor individu terhadap pengambilan keputusan investasi dan menguji validitas teori prilaku didalam penelitian ini. Pendekatan penelitian kuantitatif digunakan dalam penelitian ini dengan jumlah sampel 275 responden dan menggunakan metode analisis Structural Equation Model (SEM) dengan program SPSS AMOS. Hasil penelitian menunjukkan bahwa past behaviour tidak berpengaruh terhadap intention to invest. Attitude, subjective norms, perceived behavioural control berpengaruh terhadap intention to invest. Financial literacy berpengaruh terhadap attitude dan perceived behavioural control. serta past behaviour tidak berpengaruh terhadap attitude. Hasil penelitian ini dapat membantu investor untuk lebih mewaspadai risiko kerugian pasar saham dari saham yang dibeli. Selain itu, investor perlu lebih mengenal keuangan, risiko investasi, dan cara menghadapi risiko investasi di bursa.